CorkOakDB—The Cork Oak Genome Database Portal. (31st December 2020) - Arias-Baldrich, Cirenia; Silva, Marta Contreiras; Bergeretti, Filippo; Chaves, Inês; Miguel, Célia; Saibo, Nelson J M; Sobral, Daniel; Faria, Daniel; Barros, Pedro M
Abstract: Quercus suber (cork oak) is an evergreen tree native to the Mediterranean basin, which plays a key role in the ecology and economy of this area. Over the last decades, this species has gone through an observable decline, mostly due to environmental factors. Deciphering the mechanisms of cork oak's response to the environment and getting a deep insight into its biology are crucial to counteract biotic and abiotic stresses compromising the stability of a unique ecosystem. In the light of these setbacks, the publication of the genome in 2018 was a major step towards understanding the genetic make-up of this species. In an effort to integrate this information in a comprehensive, accessible and intuitive format, we have developed The Cork Oak Genome Database Portal (CorkOakDB). The CorkOakDB is supported by the BioData.pt e-infrastructure, the Portuguese ELIXIR node for biological data. The portal gives public access to search and explore the curated genomic and transcriptomic data on this species. Moreover, CorkOakDB provides a user-friendly interface and functional tools to help the research community take advantage of the increased accessibility to genomic information. A study case is provided to highlight the functionalities of the portal. CorkOakDB guarantees the update, curation and data collection, aiming to collect data besides the genetic/genomic information, in order to become the main repository in cork oak research. Database URL: http://corkoakdb.org/